The Effectiveness of Using Flashcard to Improve Students’ Vocabulary Mastery - Syamsiyah, Nur; Ma’rifatulloh, Sayid (Journal of Science and Education Research, 2023)
Students' English language skills are still inadequate, according to preliminary research conducted by the researcher at MTs Salafiyah Syafi'iyah Seblak Diwek Jombang. One of the causes of low student ability is the lack of vocabulary mastery. So, the researcher has taken the initiative to use flashcard media. The purpose of the study was to determine the effectiveness of students' vocabulary mastery before and after being taught using flashcards.  The researcher has used a pre-experimental design, consisting of pre-test, treatment, and post-test. The study population was 108 students of class VII MTs Salafiyah Syafi'iyah Seblak Diwek Jombang. The sample was 19 students of class VII-D using purposive sampling. The study population was 108 students of class VII-D MTs Salafiyah Syafi’iyah Seblak Diwek Jombang. The sample was 19 students of class VII-D using purposive sampling. To collect data on students' vocabulary knowledge, the researcher has used pre-test and post-test as research instruments. The test was an objective test, which consisted of 25 multiple-choice questions. The researcher used a t-test to test the data and obtained Sig. (2-tailed) less than 0.05. Then it is stated that Ha has been accepted. This has shown that there is a considerable variation in the average score of students' vocabulary acquisition before and after being taught in the classroom by using flashcards. After collecting the data, the researcher received before and after test results, with a pretest mean score of 74.32 and a posttest mean score of 90.53. Based on the results of the data analysis, many conclusions have been obtained. Namely, before using flashcards, students' vocabulary was lower than after using flashcards. Students' vocabulary before and after teaching using flashcards. Thus, it has been concluded that flashcard media has been useful in the vocabulary of students of class VII D MTs Salfiyah Safi'iyah Seblak Diwek Jombang.